(untitled) (Portuguese Journal of Family Medicine and General Practice, 2025)
Introduction: Health literacy is becoming increasingly important in health policies worldwide. It is crucial to develop tools to measure literacy levels in palliative care. Objectives: The main objective was to determine the level of knowledge of non-health professionals regarding palliative care. As a secondary objective, we aimed to develop and validate a tool to measure palliative care literacy among non-health professionals. Methods: An online inquiry was developed and directed to non-health professionals, covering demographic, professional, and academic characteristics and dichotomic questions on the concept, objective, and palliative care-specific treatments. Results: A total of 560 inquiries were analysed. Participants considered themselves to have a low level of knowledge of palliative care (4.38±2.17), but they showed a mean number of right questions higher than the median value in every dimension. Positive, moderate, and very significant positive correlations were found on own perception of the level of knowledge on palliative care in the three dimensions of the literacy scale: care focus (r=0.373; p<0.001); care process (r=0.410; p<0.001); concept (r=0.328; p<0.328). The three dimensions showed good internal consistency and global homogeneity. Discussion: Despite the low level of knowledge about palliative care among the participants, this population showed several correct answers above the median value in each dimension. This can be explained by the high academic level of the participants. Conclusion: This tool is an important step in the characterization of health literacy in palliative care in Portugal, allowing the identification of education gaps that might motivate an urgent intervention and development of specific health policies.